Brand engagement in self-concept for influencer marketing: the role of product involvement as a moderator / Chin Jing Xuan ... [et al.] - Xuan, Chin Jing; Liat, Cheng Boon; Chalke, *Anuja; Idris, Izian (2023)
Despite the rise of influencer marketing in creating brand engagement with customers on social media platforms, there exists limited understanding about the factors that contribute to brand engagement in self-concept (BESC) among social media followers. BESC is instrumental in increasing a brand's perceived value and word of mouth. This study aims to investigate the influencer-based factor (perceived influence), alongside consumer centric factors (value co-creation and social media marketing [SMM] activities) as antecedents for BESC in the influencer marketing context. Furthermore, the study tests the moderating role of product involvement on these relationships. Responses were collected through a self-administered online questionnaire which yielded a sample of 202 social media users in Malaysia. Analysis through IBM SPSS demonstrated that value co-creation and SMM activities of influencer-endorsed brands are significant predictors of BESC, while perceived influence does not contribute to BESC. Furthermore, product involvement exerted a moderating effect on all three direct relationships of perceived influence, value co-creation, and SMM activities on BESC. The research framework contributes to a greater understanding of BESC antecedents and the role of product involvement in influencer marketing context. The higher the level of product involvement, the larger the propensity for followers to form BESC through recommendations of influencers. This study can be beneficial to marketing managers that are building their own influencer marketing campaigns through incorporating value co-creation and SMM activities in their brand engagement strategy.